Present But Silent at the Council of Nicaea: Interrogating the Exegetical Error of Theologies on Women in the Church in the Quest for Unity - Kapolyo-Musonda, Precious (International review of mission, 2025)
The Council of Nicaea of 325 CE was a significant moment in the history of the church, as it not only protected the very foundation of Christian beliefs but also preserved the unity of the church. Although we are about to celebrate the 1700th anniversary of the council, women are still fighting to find their place at the table of critical church decision-making processes. Doctrines and sometimes exegetical theological error driven by patriarchy have been used as tools to silence the voice of women in the church. Although the Council of Nicaea was called to respond to a theological error, it is vital that the 1700th-anniversary celebration creates another platform to challenge the theological posture that has relegated women in the church to non-essential duties. This inspires the spirit of Nicaea, which allowed for theological arguments to be heard as a means of charting the way forward to make the church stronger, despite the threat posed by Arianism.